Risk Production at a Global Scale: Ethical Questions and Social Responsibility - Čaldarović, Ognjen (2001)
The notion of risk is discussed as an ethical dimension concerning the people, the land and wider environment. Social responsibility of stakeholders and other actors is also discussed. It is concluded that risk management in a contemporary soceity implies also a deep ethical dimensions that must be incluided in the analysis.
ENG